Cigarette brand loyalty among smokers in six European countries: Findings from the EUREST-PLUS ITC Europe Surveys - Nogueira, Sarah O. (Tob Induc Dis, 2019)
INTRODUCTION: This study aims to describe the degree of smokers’ loyalty to a specific brand of tobacco products and the variables related to choosing a specific brand among smokers in six European countries. METHODS: A cross-sectional analysis was conducted for a representative sample of adult smokers from Germany, Greece, Hungary, Poland, Romania, and Spain (approximately 1000 smokers per country). The prevalence of smokers’ having a usual brand of cigarettes smoked (factory-made or roll-yourown cigarettes), the brand of choice, the factors for choosing a specific brand and the degree of loyalty to that brand (not at all, a little, somewhat and a lot) were assessed by country, sociodemographics and smoking-related variables. RESULTS: In total, 86.6% of the smokers reported having a usual brand. In three out of the six countries, one brand holds the loyalty of between 17.8% and 24.5% of the smokers that reported having a usual brand for factory-made cigarettes. Most participants reported being loyal ‘a lot’ to their brand of choice (44.4%). The reasons most reported for choosing a cigarette brand were the taste (83.2%) and the price (51.7%). CONCLUSIONS: Brand loyalty is high among factory-made and roll-your-own cigarette smokers in six European countries. Future research on longitudinal trends of brand loyalty to evaluate the effect of tobacco control policies in these European countries is warranted.